Effects of seed priming on salt tolerance of maize (Zea mays L.) seedlings by lipo-chitooligosaccharide - Nandhini, D Udhaya; Somasundaram, E (Bangladesh Journal of Botany, 2022)
Effects of lipo-chitooligosaccharide seed priming on agronomic traits of maize under different salt concentrations (0, 2, 4, 6 and 8 dS/m) were studied. Results showed that the effects of salinity and seed priming on agronomic characteristics were significant at the probability level of 5% (P< 0.05). The increase in salinity up to 10 dS/m negatively influenced all traits. However, seed priming with LCO @ 4ml/kg compensated the adverse effects of salinity on agronomic traits. The regression analysis under salt stress condition showed that aforesaid traits all together contributed 98.4 per cent for salt tolerance. Hence, the novel finding showed that seed priming with LCO signal molecule can enhance the maize tolerance to salinity by improving the physiological changes in seeds which has very high value of implications. Bangladesh J. Bot. 51(2): 381-385, 2022 (June)